High Lithium Storage Performance of Co Ion-Doped Li4Ti5O12 Induced by Fast Charge Transport - Wang, M.; Chen, Y.; Yang, C. X.; Zeng, Y. H.; Fang, P. F.; Wang, W.; Wang, X. L. (Frontiers in Chemistry, 2022)
In this study, Co3O4-doped Li4Ti5O12 (LTO) composite was designed and synthesized by the hydrothermal reduction method and metal doping modification method. The microstructure and electrochemical performance of the Co3O4-doped Li4Ti5O12 composite were characterized by XRD, SEM, TEM, electrochemical impedance spectroscopy, and galvanostatic tests. The results showed that Li4Ti5O12 particles attached to lamellar Co3O4 constituted a heterostructure and Co ion doped into Li4Ti5O12 lattice. This Co ion-doped microstructure improved the charge transportability of Li4Ti5O12 and inhibited the gas evolution behavior of Li4Ti5O12, which enhanced the lithium storage performance. After 20 cycles, the discharge specific capacity reached stability, and the capacity retention maintained 99% after 1,000 cycles at 0.1 A/g (compared to the capacity at the 20th cycle). It had an excellent rate performance and long cycle stability, in which the capacity reached 174.6 mA h/g, 2.2 times higher than that of Li4Ti5O12 at 5 A/g.